Magnetic Actuation Methods in Bio/Soft Robotics. (23rd December 2020) - Ebrahimi, Nafiseh; Bi, Chenghao; Cappelleri, David J.; Ciuti, Gastone; Conn, Andrew T.; Faivre, Damien; Habibi, Neda; Hošovský, Alexander; Iacovacci, Veronica; Khalil, Islam S. M.; Magdanz, Veronika; Misra, Sarthak; et al.
Abstract: In recent years, magnetism has gained an enormous amount of interest among researchers for actuating different sizes and types of bio/soft robots, which can be via an electromagnetic‐coil system, or a system of moving permanent magnets. Different actuation strategies are used in robots with magnetic actuation having a number of advantages in possible realization of microscale robots such as bioinspired microrobots, tetherless microrobots, cellular microrobots, or even normal size soft robots such as electromagnetic soft robots and medical robots. This review provides a summary of recent research in magnetically actuated bio/soft robots, discussing fabrication processes and actuation methods together with relevant applications in biomedical area and discusses future prospects of this way of actuation for possible improvements in performance of different types of bio/soft robots. Abstract : This comprehensive review provides a summary on recent research in magnetically actuated bio/soft robots, discussing actuation methods and fabrication processes together with relevant state‐of‐the art applications in the biomedical field and deliberates future prospects of this novel method of actuation for possible improvements in performance of various types of bio/soft robots.